2023
DOI: 10.3389/fnmol.2023.1239599
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels in cancer-induced bone pain: from molecular mechanisms to clinical applications

Huan-Jun Lu,
Xiao-Bo Wu,
Qian-Qi Wei

Abstract: Cancer-induced bone pain (CIBP) caused by bone metastasis is one of the most prevalent diseases, and current treatments rely primarily on opioids, which have significant side effects. However, recent developments in pharmaceutical science have identified several new mechanisms for CIBP, including the targeted modification of certain ion channels and receptors. Ion channels are transmembrane proteins, which are situated on biological cell membranes, which facilitate passive transport of inorganic ions across me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Patients with low circadian rhythm circadian rhythm signature (CRS) may have a higher TMB and are more likely to benefit from immune checkpoint blocking (ICB) therapy 46 . In the GO pathway enriched by KCNQ4, a large number of studies have shown that the transmembrane transport and concentration of ion channels as transmembrane proteins are also closely related to cancer 47 51 .Recent studies have found that plasma membrane disturbance and tumor cell lysis can be an integral part of multimodal therapy strategies for cancer patients through oncolytic polymers as new targets and killing mechanisms 52 . The glycoprotein interaction on the cell surface can participate in immune escape 53 .Inositol 1, 4, 5-triphosphate (IP3Rs) acts as a channel for intracellular calcium (Ca) 2 + to release cellular bioenergetics and participates in cell proliferation and death in cancer 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low circadian rhythm circadian rhythm signature (CRS) may have a higher TMB and are more likely to benefit from immune checkpoint blocking (ICB) therapy 46 . In the GO pathway enriched by KCNQ4, a large number of studies have shown that the transmembrane transport and concentration of ion channels as transmembrane proteins are also closely related to cancer 47 51 .Recent studies have found that plasma membrane disturbance and tumor cell lysis can be an integral part of multimodal therapy strategies for cancer patients through oncolytic polymers as new targets and killing mechanisms 52 . The glycoprotein interaction on the cell surface can participate in immune escape 53 .Inositol 1, 4, 5-triphosphate (IP3Rs) acts as a channel for intracellular calcium (Ca) 2 + to release cellular bioenergetics and participates in cell proliferation and death in cancer 53 .…”
Section: Discussionmentioning
confidence: 99%
“…DRG, dorsal root ganglion; IL-6, interleukin-6; TNFα, tumor necrosis factor-α; PGE2, prostaglandin E2; P2XR, purinergic P2X receptor; Piezo, mechanosensitive ion channel. Figure reproduced with permission from [ 27 ].…”
Section: Figurementioning
confidence: 99%
“…CIBP usually emerges from tumors and associated stromal cells releasing several mediators (cytokines, chemokines, and prostaglandins), cancer growth compressing the spinal cord and bone neuronal terminals, and tumor-bearing bone fractures. Consequently, the combination of all these aspects leads to pain, hypercalcemia, anemia, increased susceptibility to infections, spinal instability, and decreased mobility [37][38][39].…”
Section: Cancer Pain Mechanismsmentioning
confidence: 99%
“…The activation of non-TRP channels, such as Piezo (involved in the conversion of mechanical stimuli into electrical signals) [44], P2X receptors (activated by extracellular adenosine triphosphate [ATP]) [45], acid-sensing ion channels (ASICs, sensitive to extracellular acidification as detected in the tumor microenvironment) [46], and cannabinoid receptors (CB1, expressed in the central nervous system and nerve terminals, and CB2 in the immune system), also acts to control the transduction of pain from nociceptive stimuli, the production of inflammatory cytokines by the nerves and immune cells, and the activation of sensory neurons [39].…”
Section: Cancer Pain Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation